Analisis Pengendalian Kualitas Produk Roti Kering dengan Menggunakan Metode Statistical Quality Control (SQC) untuk Mengurangi Produk Cacat - Anisa Nurfitri Woisiri; Muhardi; Eka Tresna Gumelar (UNISBA Press, 2022)
Abstract. Golden Bakery Cianjur is a bakery industry whose production activities are still not accompanied by quality control so that there are still many defective products that are forced to be sold to the market. The purpose of this study is to find out how the quality control is carried out by Golden Bakery Cianjur, and the analysis uses statistical quality control (SQC) methods. The research method used is descriptive quantitative with data collection techniques namely observation, interviews, and documentation. The data analysis stage begins with making check sheets, histograms, scatter charts, Pareto charts, Np control charts, and fishbone charts. The results showed that there were three types of dry bread defects, namely defects in the level of maturity that were not appropriate, size and shape were not the same, and broken. Pareto chart shows the type of product damage is more dominant in the size and shape defects are not the same by 72%, the results of the control chart analysis show special cause of variation deviations. Fishbone chart shows the causes of disability are from human factors, methods, machines, materials and media (environment). Actions that need to be taken to reduce defective products are creating and implementing Standard Operating Procedures (SOP), conducting workforce training, using one size bread slicer machine, and modifying the oven by adding a timer and temperature controller. Abstrak. Golden Bakery Cianjur merupakan industri roti yang dalam kegiatan produksinya masih belum disertai pengendalian kualitas sehingga masih terdapat banyak produk cacat yang terpaksa ikut dijual ke pasar. Tujuan dari penelitian ini untuk mengetahui bagaimana pengendalian kualitas yang dilakukan Golden Bakery Cianjur, serta analisisnya menggunakan metode statistical quality control (SQC). Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan teknik pengumpulan data yakni observasi, wawancara, dan dokumentasi. Tahapan analisis data dimulai dengan membuat check sheet, histogram, scatter chart, pareto chart, control chart Np, dan fishbone chart. Hasil penelitian menunjukkan terdapat tiga jenis cacat roti kering yakni cacat tingkat kematangan tidak sesuai, ukuran dan bentuk tidak sama, dan patah. Pareto chart memperlihatkan jenis kerusakan produk lebih dominan pada cacat ukuran dan bentuk tidak sama sebesar 72%, hasil analisis control chart menunjukkan adanya penyimpangan special cause of variation. Fishbone chart menunjukkan penyebab kecacatan adalah dari faktor manusia, metode, mesin, material dan media (lingkungan). Tindakan yang perlu dilakukan untuk mengurangi produk cacat yaitu membuat dan menerapkan Standar Operasional Prosedur (SOP), melakukan pelatihan tenaga kerja, menggunakan satu ukuran mesin bread slicer, dan memodifikasi oven dengan menambahkan pengatur waktu dan suhu.